Severe polycystic liver disease: An unsual cause of chronic Budd-Chiari Syndrome - Aboutarik Fatima Ezzahra; Dassouli Cherihane; Ait Errami Adil; Oubaha Sofia; Samlani Zouhour; Krati Khadija (Archives of Clinical Gastroenterology - Peertechz Publications, 2022)
Autosomal dominant polycystic kidney disease is a hereditary disease, characterized by the development of cysts in the renal parenchyma with extra-renal manifestations. Liver damage is rarely a source of complications. A Budd-Chiari syndrome could occur following the compression of the supra-hepatic veins by the cysts. It is an exceptional mechanical complication.  We present a case of a 54 year old woman, with a diagnostic of an asymptomatic autosomal dominat polycystic kidney disease since childhood was admitted to our hospital due to significantly increased abdominal girth. The physical examination showed grade III ascites. A paracentesis for relief at admission disclosed an exudative fluid. A abdominal computed tomographic scan showed multiples cystic lesions in the kidneys and liver, with a large hepatic cyst responsible for compression of the suprahepatic veins and the inferior vena cava resulting in chronic Budd-Chiari syndrome. The treatment was radiological drainage followed by percutaneous sclerosis of cysts to alleviation of the compression. Unfortunately, the patient died a few days after an intraperitoneal cystic rupture.